Scale-Invariant Endogenous Growth. - Carl-Johan Dalgaard; Claus Thustrup Hansen (University of Copenhagen, Economic Policy Research Unit (EPRU), 2000)
In this paper we develop a theory of scale-invariant endogenous growth. By this we mean a theory capable of generating a balanced growth path where both the growth rate and the level of GDP per capita are independent of the size of population, where population growth is neither necessary nor conductive for economic growth, and where economic incentives and policy matter for growth. Such a theory arises naturally when endogenous skill formation is added to a basic R&D driven growth model featuring diminishing returns to existing knowledge in creating new ideas.
Keywords: 330